Effect of sodium arsenite on the biosynthesis of mitomycins by Streptomyces caespitosus and mode of action of mitomycin C on Bacillus subtilis NRRL B-543 - Abou-Zeid, A A; Yousef, A A (Folia microbiologica, 1976)
Addition of different concentrations of sodium arsenite to the fermentation medium used for the production of mitomycin antibiotics by Streptomyces caespitosus hindered the biosynthesis of mitomycins and led to the accumulation of 2-oxoglutarate, pyruvate and acetone. Mitomycin C isolated and purified using thin-layer chromatography in low concentration of about 0.1 mug/ml did not affect the RNA, DNA and protein biosynthesis of the growing Bacillus subtilis, while at 10 mug/ml mitomycin C markedly affected RNA, DNA and protein biosynthesis.
Keywords: mitomyciny; DNA, Bacterial; RNA, Bacterial; Streptomyces; Arsenic; Bacillus subtilis; aceton; DNA bakterií; Bacterial Proteins; pyruváty; bakteriální RNA; kyseliny ketoglutarové; Acetone; Mitomycins; Pyruvates; fermentace; Ketoglutaric Acids; Fermentation; arsen; bakteriální proteiny